Equivalent Expressions are expression that have the same value on both side of the equal sign.
Expression 1:
First simplify both sides of the expression. One of them are already fully simplified.
8x-4y=4(-y+2x)
8x- 4y=-4y+8x
This expression IS an equivalent expression.
Expression 2:
Do the same as in expression one (we will be simplifying all of the expressions).
8x+4y=4(2x+y)
8x+4y=8x+4y
This expression IS an equivalent expression.
Expression 3:
4x-8y=4(-x+2y)
4x-8y=-4x+8y
This expression IS NOT an equivalent expression.
Expression 4:
4x+8y=4(x+2y)
4x+8y=4x+8y
This expression IS an equivalent expression.
Expression 5:
4x+8y=4(8xy)
4x+8y=32xy
This expression IS NOT an equivalent expression.